Nanoscopic Visualization of Soft Matter Using Fluorescent Diarylethene Photoswitches. Issue 41 (13th September 2016) - Nevskyi, Oleksii; Sysoiev, Dmytro; Oppermann, Alex; Huhn, Thomas; Wöll, Dominik
Abstract: The in situ imaging of soft matter is of paramount importance for a detailed understanding of functionality on the nanoscopic scale. Although super‐resolution fluorescence microscopy methods with their unprecedented imaging capabilities have revolutionized research in the life sciences, this potential has been far less exploited in materials science. One of the main obstacles for a more universal application of super‐resolved fluorescence microscopy methods is the limitation of readily available suitable dyes to overcome the diffraction limit. Here, we report a novel diarylethene‐based photoswitch with a highly fluorescent closed and a nonfluorescent open form. Its photophysical properties, switching behavior, and high photostability make the dye an ideal candidate for photoactivation localization microscopy (PALM). It is capable of resolving apolar structures with an accuracy far beyond the diffraction limit of optical light in cylindrical micelles formed by amphiphilic block copolymers. Abstract : Enlightened soft matter : A diarylethene photoswitch with a dark open and a fluorescent closed form serves as a novel and robust label for super‐resolved photoactivation localization microscopy (PALM) of apolar soft‐matter structures. Its applicability is rationalized on the basis of suitable photochemical switching kinetics.